Analysis of the Profit and Loss Statement to Determine the Profit Contribution of the Room Department at Mustika Tuban Hotel: Analisa Laporan Laba Rugi Untuk Menentukan Kontribusi Laba Departemen Kamar Pada Hotel Mustika Tuban - Yuanis Yuanis; Wasito Wasito; Fitriya Rahayu Ningsih (Universitas Muhammadiyah Sidoarjo, 2020)
Hotel services are one of the supporting facilities for promoting Indonesian tourism. Hotel activities are renting rooms, selling food, drinks and providing commercial visitor services. These supporting facilities are intended to increase the attractiveness of guests, so that guests are expected to feel at home and have a long stay at the hotel. The purpose of this study is to determine the income, operating costs of the room to the profit of the departmental room at Hotel Mustika Tuban. This research uses descriptive qualitative research method to get a picture of the situation in the field through observation, interviews, documentation, and literature review. Based on the results of the calculation of the allocation of operating expenses (operating expenses) in the room department, a departmental income statement can be prepared for each type of room, so that the proportion of operating expenses and departmental income of each room type can also be calculated in each period. Based on the above, the researcher concluded that the revenue of the room department is strongly influenced by the rate of occupation, considering that the proportion of operating expenses is very low. Apart from these costs, there are still many undistributes expenses that leave the owner's profit. Most of these costs are fixed. Therefore, the importance of a more intensive and creative marketing program to attract guests, given the large number of accommodation capacities and an increase in the volume of occupancy rates.